2020
DOI: 10.17511/ijpr.2020.i02.01
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological profile of paediatric patients with thalassemia major

Abstract: Background:The average prevalence of beta-thalassemia major is 3-4% which translates to 35-45 million carriers. Repeated use of blood transfusion in these patients causes significant morbidity and associated adverse effects. Aims and Objective: To study the clinical profile and laboratory parameters of Thalassemia major patients between the age group 1-14 years. . This included history, anthropometry, clinical examinations (general and systemic examinations) and laboratory Investigations including serum ferrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The age distribution of the study population revealed a significant proportion of children aged 1-5 years (54%), which is consistent with previous studies (Sharma et al; 9 Harish and Pasha; 10 and Al-Kherbash et al, 11 ) This observation highlights the early onset of thalassemia major and the need for early diagnosis and management.…”
Section: Discussionsupporting
confidence: 90%
“…The age distribution of the study population revealed a significant proportion of children aged 1-5 years (54%), which is consistent with previous studies (Sharma et al; 9 Harish and Pasha; 10 and Al-Kherbash et al, 11 ) This observation highlights the early onset of thalassemia major and the need for early diagnosis and management.…”
Section: Discussionsupporting
confidence: 90%